Space variability of Swietenia macrophylla in agroforestry system in the brasilian Amazon - Costa, Luiz Rodolfo Reis; Dolácio, Cícero Jorge Fonseca; Zea-Camaño, Jorge Danilo; Oliveira, Rudson Silva; Pelissari, Allan Libanio; Maciel, Maria de Nazaré Martins (Instituto de Ecología, A.C., 2020)
To characterize the spatial variation behavior of the tree attributes of tropical species in agroforestry systems is important for its management, and in this sense, geostatistics stands out for using techniques able of characterizing this variation. In this work, geostatistical methods were used to evaluate and map spatial variability of diameter (dbh) at 1.3 m from the ground level, commercial height (hc) and commercial volume (vc) of trees Swietenia macrophylla King, planted in an agroforestry system in the Brazilian Amazon. The field sampling was carried out based on a grid of 50 m × 50 m, which resulted in 36 systematics point. At each point, a circular plot of 500 m2 was installed to measure the variables dbh, hc. The vc of trees in the portions was estimated with the best equation adjusted to the 108 trees cubing data. Next, the spatial distribution standard of these variable were modeled with geostatistics and ordinary kriging was used to generate maps with predictions and uncertainties of the variables. The Schumacher-Hall’s model resulted in the best equation for the estimation of vc, and the systematic grid was efficient to detect the spatial patterns of these variables, because the adjusted semivariograms models demonstrated the strong spatial dependence on the dbh, hc and vc, being possible, make precise interpolations, generating cross-validation results without trend, mainly for vc that presented the best adjusted theoretical model.